2014
DOI: 10.2214/ajr.14.12588
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Tumor Imaging With 68Ga-DOTA-NOC: Physiologic and Benign Variants

Abstract: Previously unreported benign sites of 68Ga-DOTA-NOC uptake were found in the majority of studies, suggesting the presence of somatostatin receptors in physiologic variants or processes with no evidence of tumor. Knowledge of increased tracer uptake in non-NET-related sites is important for accurate interpretation and for avoiding potential pitfalls of 68Ga-DOTA-NOC PET/CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
3
15
0
3
Order By: Relevance
“…They found 29 sites of diffuse 68Ga-DOTA-NOC uptake in the breasts in 14 of the 96 female patients with SUVmax range of 0.8-2.7. Low and variable expression of SSTR 2 has been reported in breast tissue unaffected by disease (8). In our case, we demonstrated Ga-68 DOTA-TATE uptake in the bilateral breasts in a nursing patient newly diagnosed with NET.…”
Section: Discussionsupporting
confidence: 59%
“…They found 29 sites of diffuse 68Ga-DOTA-NOC uptake in the breasts in 14 of the 96 female patients with SUVmax range of 0.8-2.7. Low and variable expression of SSTR 2 has been reported in breast tissue unaffected by disease (8). In our case, we demonstrated Ga-68 DOTA-TATE uptake in the bilateral breasts in a nursing patient newly diagnosed with NET.…”
Section: Discussionsupporting
confidence: 59%
“…[ 68 Ga]DOTA-labeled somatostatin analogues bind specifically to somatostatin receptors (SSTRs) and are commonly used for imaging and treatment planning of neuroendocrine tumors (NETs) [3][4][5][6][7][8]. Moreover, [ 68 Ga]DOTA-labeled somatostatin analogues have been reported to show higher sensitivity for the detection of NETs and other somatostatin-receptor expressing tumors than the most widely used radiotracer, 2-deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]FDG), which is used to measure glucose metabolism [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…68 Ga-DOTA-NOC (t 1/2 = 68 min) is an octreotide analogue that binds somatostatin receptors. In a retrospective review of diagnostic 68 Ga-DOTA-NOC-PET scans, Kagna et al reported increased 68 Ga-DOTA-NOC uptake in fat depots linked to BAT only in 1% of patients (Kagna et al 2014). Considering the very low prevalence of increased uptake of 68 Ga-DOTA-NOC in BAT, it is unlikely that it can be used for the assessment of BAT.…”
Section: -(Rs)-[ 18 F]fluoro-6-thiaheptadecanoic Acid (Ftha)mentioning
confidence: 99%
“…reported increased 68 Ga‐DOTA‐NOC uptake in fat depots linked to BAT only in 1% of patients (Kagna et al . ). Considering the very low prevalence of increased uptake of 68 Ga‐DOTA‐NOC in BAT, it is unlikely that it can be used for the assessment of BAT.…”
Section: Introductionmentioning
confidence: 97%